Effects of Certain cis-Regulatory Elements on Stage-Specific vitellogenin Expression in the Bombyx mori (Lepidoptera: Bombycidae). Issue 3 (18th June 2020) - Shen, Guanwang; Liu, Hongling; Lin, Ying; Xing, Dongxu; Zhang, Yujing; Xia, Qingyou
Abstract: Bombyx mori vitellogenin ( BmVg ) is highly upregulated during pupation, and the 20-hydroxyecdysone and amino acids may regulate stage-specific BmVg expression. However, previous studies showed that other factors may also affect stage-specific BmVg expression. Here, we characterized effective BmVg transcription factors by identifying the corresponding cis -regulatory elements (CREs). We prepared transgenic B. mori, in which DsRed was driven by various lengths of BmVg promoter. qRT-PCR analysis showed that DsRed expression driven by a 1.0-kb BmVg promoter (VgP1.0K) was consistent with endogenous BmVg . VgP1.0K specificity was closer to the endogenous BmVg promoter than that of VgP0.8K. These results suggest that CREs affecting stage-specific BmVg expression were localized to the 1.0-kb BmVg promoter. We investigated the effects of certain CREs that could influence the stage specificity of BmVg promoter on BmVg expression in transgenic B. mori . The relative DsRed expression was significantly reduced in transgenic female B. mori and the peak in DsRed expression was delayed after E-box CRE mutation. These results demonstrate that the E-box element enhanced BmVg expression and also affected stage-specific BmVg expression. Moreover, the relative DsRed expression was significantly increased in transgenic female of B. mori after 3×BD CRE mutation in BmVg promoter. However, the stage specificity of the mutated promoter was consistent with that of the endogenous BmVg promoter. The 3×BD element downregulated BmVg but had no effect on stage-specific BmVg expression. The present study promoted the process of elucidating the regulatory network for stage-specific BmVg expression and furnished a theoretical basis for the application of BmVg promoter.